Sistem Pakar Diagnosa Kerusakan Smartphone Menggunakan Metode Certainty Factor - Ilham Agus Pratama; Aldo Erianda; Ardi Syawaldipa (SOTVI - Society of Visual Informatics, 2026)
Smartphones are multifunctional telecommunication devices that have become an essential part of everyday life. However, with the increasing use of smartphones, damage to these devices often occurs and is difficult for lay users to detect. To assist Pagaruyung Ponsel employees or cashiers in diagnosing smartphone damage without needing to rely on expert technicians, this study developed a computer-based expert system. This system combines the Forward Chaining and Certainty Factor (CF) methods to accurately detect smartphone damage. By utilizing expert knowledge, this system provides appropriate solutions based on detected symptoms. The system's accuracy test results showed a value of 85%, which proves the system's effectiveness in providing accurate diagnoses. It is hoped that this system can facilitate independent smartphone diagnosis and repair anytime and anywhere, through a website-based platform. The implementation of this expert system with the Forward Chaining and Certainty Factor (CF) methods is expected to increase the speed and efficiency in handling smartphone damage problems